Beyond trauma? Memories of Joi/y and memory play in Blade Runner 2049. (February 2019) - Arnold-de Simine, Silke
Cultural memory studies finds itself at an impasse: whereas 'cultural memory' is conceptualized as mediated, dynamic, imaginative and shaped by the present, the dominant paradigm of 'trauma' illuminates the hold the past has on us, casting the shadow of a melancholic subjectivity that threatens to obscure our agency as (political) subjects. This article asks what lies in store for memory studies beyond the focus on (classic) trauma (theory). Using the movie Blade Runner 2049 (US 2017; dir: Denis Villeneuve) as an illustrative example, it explores how creative and joyful forms of meaning-making through play and acts of memory inform each other in what the psychoanalyst DW Winnicott described as 'cultural experience'.